Agency and Identity in the Collective Self. (February 2022) - Shteynberg, Garriy; Hirsh, Jacob B.; Garthoff, Jon; Bentley, R. Alexander
Contemporary research on human sociality is heavily influenced by the social identity approach, positioning social categorization as the primary mechanism governing social life. Building on the distinction between agency and identity in the individual self ("I" vs. "Me"), we emphasize the analogous importance of distinguishing collective agency from collective identity ("We" vs. "Us"). While collective identity is anchored in the unique characteristics of group members, collective agency involves the adoption of a shared subjectivity that is directed toward some object of our attention, desire, emotion, belief, or action. These distinct components of the collective self are differentiated in terms of their mental representations, neurocognitive underpinnings, conditions of emergence, mechanisms of social convergence, and functional consequences. Overall, we show that collective agency provides a useful complement to the social categorization approach, with unique implications for multiple domains of human social life, including collective action, responsibility, dignity, violence, dominance, ritual, and morality.